Pembelaan Terpaksa Melampaui Batas (Noodweer Exces) dalam Perkara Pidana Putusan Nomor 34/PID.B/2020/PN MII - Elmina A Herysta; Faisal Faisal; Toni Toni; Ibrohim Ibrohim (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2023)
This research examines Decision Number 34/Pid.B/2020/ PN MII in the case of loss of life of another person cannot be convicted because it is based on forced defense beyond the limit or noodweer exces. Noodweer exces is a defense when a person experiences an attack or threat of attack, the exceeding of the limits of a defense must be due to the influence of a great mental shock. The purpose of this study is to determine the applicability of noodweer exces in criminal case number 34/Pid.B/2020/ PN MII and to determine the criminal liability of the perpetrator in Decision Number 34/Pid.B/2020/ PN MII in terms of forced defense beyond the limit. The type of research used is normative juridical with a case approach method. The results showed that noodweer exces could not be applied because the shooting of the victim's head by the defendant Sumantri was not caused directly by severe mental shock. According to the Theory of necessary defense, the defense must be proportional to the nature of the attack. Because the element of necessity defense is not fulfilled and the defendant's actions fulfill the element of negligence, the defendant can be convicted as formulated in Article 359 of the Criminal Code.Â Â